Early Return to Play After Intramedullary Screw Fixation of Acute Jones Fractures in Collegiate Athletes: 22-Year Experience. Issue 4 (24th April 2020) - Watson, Scott; Trammell, Amy; Tanner, Stephanie; Martin, Steven; Bowman, Larry
Background: There is disagreement among team physicians, without conclusive evidence, as to when high-level athletes with a Jones fracture should be allowed to return to play after being treated operatively with an intramedullary screw. Purpose: To report our experience of early return to sport in collegiate athletes after intramedullary screw fixation of Jones fractures. Study Design: Case series; Level of evidence, 4. Methods: We identified all collegiate athletes with an acute fracture at the base of the fifth metatarsal treated by 1 of 2 orthopaedic surgeons with intramedullary screw fixation over a 22-year period (1994-2015), and we performed a retrospective review of their records. Fixation consisted of a single intramedullary screw. Athletes were allowed to bear weight as tolerated in a walking boot immediately postoperatively and return to play as soon as they could tolerate activity. Patients were contacted to complete patient-reported outcome scores that included the Foot and Ankle Ability Measure (FAAM) score, a brief survey specific to our study, and follow-up radiographs. Results: A total of 26 acute Jones fractures were treated in 25 collegiate athletes (mean age, 20 years; range, 18-23 years). Overall, the athletes returned to play at an average of 3.6 weeks (range, 1.5-6 weeks). Three screws were removed for symptomatic skin irritation. There was 1 refracture after screw removal that was done after radiographic and clinical documentation of fracture union, which was treated with repeat cannulated percutaneous screw fixation. One screw was observed on radiographs to be broken at 1 year postoperatively, but the fracture was healed and the athlete was playing National Collegiate Athletic Association Division I sports without symptoms and continued to play professionally without symptoms. Of 25 athletes, 19 completed the FAAM at an average follow-up of 8.6 years (range, 1.5-20.0 years). They reported scores of 94.9% (range, 70.2%-100%) for the activities of daily living subscale and 89.1% (range, 42.9%-100%) for the sports subscale. Follow-up radiographs were obtained, and no nonunion, malunion, or additional hardware complications were identified. Conclusion: Athletes with acute Jones fractures can safely be allowed to return to play after intramedullary screw fixation as soon as their symptoms allow, without significant complications. In our experience, this is usually within 4 weeks from injury.